2017
DOI: 10.1111/disa.12260
|View full text |Cite
|
Sign up to set email alerts
|

Citizen participation in disaster recovery projects and programmes in rural communities: a comparison of the Haiti earthquake and Hurricane Katrina

Abstract: This study investigates predictors of local participation in recovery projects and programmes following Hurricane Katrina in the United States in 2005 and the earthquake in Haiti in 2010. Using two sets of survey data, it examines whether disaster impacts and social capital (social trust and civic engagement) are associated with disaster recovery participation and compares predictors of such engagement in the two locations. Multivariate logistic regression results reveal that physical injuries, limited communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Community members mobilized by local government or by community self-organization had many differences in social characteristics. Studies [53,54] discuss the relationship between the social characteristics of community members and community participation generally, and do not consider the mobilization factors of local government.…”
Section: Significant Difference Between Villagers Who Are Mobilized Bmentioning
confidence: 99%
“…Community members mobilized by local government or by community self-organization had many differences in social characteristics. Studies [53,54] discuss the relationship between the social characteristics of community members and community participation generally, and do not consider the mobilization factors of local government.…”
Section: Significant Difference Between Villagers Who Are Mobilized Bmentioning
confidence: 99%
“…Hicks et al demonstrated that citizens' participation led to global mapping and resulted in enhancing the disaster reduction [6]. They showed how a real-time natural disaster In fact, when disaster strikes, because citizens are present at the scene of a disaster, they can be the "true" first responders, who can actively address community needs by participating in activities such as the restoration of public services and infrastructure [22][23][24][25][26][27]. Therefore, the government expects more efficient solutions by encouraging individuals to participate in disaster management.…”
Section: Introductionmentioning
confidence: 99%
“…However, the achievement of civic engagement is a key ingredient for building trust in such actors and, consequently, for fostering benevolence and support for their decisions (Harvey, ). To realise civic engagement, the use of an adequate crisis response communication strategy is crucial, as it allows citizens to: (i) understand the actions taken by such entities (Sciulli, ); (ii) respond to their decisions (Nussbaum, ); and (iii) collaborate with them to enhance the management of disasters (Pyles et al, ).…”
Section: Introductionmentioning
confidence: 99%